Anorectic effect, biochemical and hematological profiles of alkaloid extract from Mitragyna speciosa Korth. in rats - Ekkasit Kumarnsit,; Niwat Keawpradub,; Narumon Sengnon,; Juraithip Wungsintaweekul,; Dania Cheaha, (Penerbit Universiti Kebangsaan Malaysia, 2021)
There is an on-going debate about medicinal use of kratom plant (Mitragyna speciosa (MS)) on whether it has beneficial or adverse effects. This study aimed to examine long-term weight-reducing effects, toxicity, and dopamine pathway activation of MS alkaloid extract on adult male Wistar rats. In anorexic study, the rats were divided into 3 groups (n = 10), receiving intragastric administration once a day for 19 weeks as control (distilled water), chronic (20 mg/kg MS alkaloid extract) and withdrawal (20 mg/kg MS alkaloid extract for week 1-12 and distilled water for week 13-19) groups. Body weights were measured daily, and blood samples were collected at the end of study for biochemical and hematological tests. In immunohistochemistry, the effects of the extract (40 and 80 mg/kg) on the nucleus accumbens (NAc) and striatum (STr) were determined by using Fos-like immunoreactivity. From week 2 to 19, the results showed a significant reduction in body weight gain produced by the extract. Cessation of the treatment at week 12 did not result in a rebound weight gain. Chronic MS alkaloid extract treatment significantly decreased non-fasting blood sugar, triglyceride, uric acid and blood urea nitrogen (BUN). However, elevated SGOT may suggest possible hepatotoxicity. Chronic MS alkaloid extract treatment also produced baseline levels for most of the hematological parameters except a decrease of monocyte. In immunohistochemistry, the acute treatment did not induce Fos-like immunoreactivity in the NAc and STr. These data demonstrated the beneficial effects of the MS alkaloid extract for possible treatment of metabolic syndromes without toxicity and rewarding effect.